Parent-Counselor Conferences: Obligation or Opportunity? - Hillman, Bill W.; Carlson, Jon (Canadian Journal of Counselling and Psychotherapy, 2012)
Many counselors avoid conferences with parents who at times can be quite defensive and aggressive. The authors give practical ideas for winning the cooperation of parents and making conferences with them an opportunity for growth rather than a dreaded obligation. Specific suggestions are given for helping parents understand their children and develop workable plans for positive change.